Modeling human liver organ development and diseases with pluripotent stem cell-derived organoids - Ouchi, Rie; Koike, Hiroyuki (Frontiers in Cell and Developmental Biology, 2023)
The discoveries of human pluripotent stem cells (PSCs) including embryonic stem cells and induced pluripotent stem cells (iPSCs) has led to dramatic advances in our understanding of basic human developmental and cell biology and has also been applied to research aimed at drug discovery and development of disease treatments. Research using human PSCs has been largely dominated by studies using two-dimensional cultures. In the past decade, however, ex vivo tissue “organoids,” which have a complex and functional three-dimensional structure similar to human organs, have been created from PSCs and are now being used in various fields. Organoids created from PSCs are composed of multiple cell types and are valuable models with which it is better to reproduce the complex structures of living organs and study organogenesis through niche reproduction and pathological modeling through cell-cell interactions. Organoids derived from iPSCs, which inherit the genetic background of the donor, are helpful for disease modeling, elucidation of pathophysiology, and drug screening. Moreover, it is anticipated that iPSC-derived organoids will contribute significantly to regenerative medicine by providing treatment alternatives to organ transplantation with which the risk of immune rejection is low. This review summarizes how PSC-derived organoids are used in developmental biology, disease modeling, drug discovery, and regenerative medicine. Highlighted is the liver, an organ that play crucial roles in metabolic regulation and is composed of diverse cell types.